Implementasi Manajemen Talenta Melalui Penilaian Kompetensi ASN Jabatan Pengawas Pemerintah Kabupaten Pekalongan - Rizka Shofrotul Muna; Andriyastuti Suratman (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2024)
Talent management in the Regulation of the Minister for Empowerment of the State Civil Apparatus and Bureaucratic Reform of the Republic of Indonesia Number 3 of 2014 is a career management system which includes acquisition, retention, development, and placement of talent to occupy positions based on the potential and competence of the State Civil Apparatus in accordance with the position qualifications position. ASN competency to be able to occupy certain positions is assessed in several ways, one of which is using a competency assessment. The Pekalongan Regency Government through the Personnel and Human Resources Development Agency (BKPSDM) has carried out a competency assessment for ASN with supervisory positions, attended by 60 participants from Regional Apparatus Organizations within the Pekalongan Regency environment. This article uses a qualitative method with a descriptive analysis approach. The data analysis technique uses data triangulation from primary data sources, namely sources, and secondary data, namely the results of competency assessments for Pekalongan Regency government supervisory positions, then elaborated to develop a conceptual framework for implementing ASN talent management through competency assessments to improve the quality of ASN. Based on this case study, a competency gap was found in the competency assessment carried out, where the highest competency gap was in the competency to develop oneself and others. The purpose of this article is to provide recommendations to the Pekalongan Regency BKPSDM for suggestions for developing ASN competencies which are used as a basis for promotions, transfers and rotations.